In accordance with Islamic law, Papuan Muslims in Kaimana City Village Apply Kafa'ah to Marriages - Irsanti, Jasmi; Hamzah, Nur Asia; Hijaz, M. Chiar (Journal of Family Law and Islamic Court, 2022)
The growth of Islam in Papua has an impact on the people's customs and culture, particularly marriage practices. This research's central issue is subdivided into a number of substance-related issues, including: 1) What is the common description of Papuan Muslim marriage in Kaimana Kota Village? 2) According to Islamic law, how does kafa'ah apply to marriages between Papuan Muslims? Researchers employed descriptive qualitative research with field research methods, two research orientations, namely the social and theological-normative (syar'i) approaches. Al-Qur'an, hadith, and a number of indigenous Papuan Muslim communities in the Kaimana Kota Subdistrict serve as the data sources for this study. In addition, observation, interviews, documentation, and reference tracking were employed for data gathering. Then, the data is processed and examined in three steps, namely data reduction, data presentation, and conclusion. The findings of this study indicate that the description of Papuan Muslim marriages in Kaimana Kota Village is identical to that of Indonesian weddings in general, with the addition of a number of customary rules that bind the process, including mate selection, igiigree, nuhijna wafen, nobune muere, measuring noses for girls, consent and qabul, and nobune muere virnee naare. The valid kafa'ah consists of two major components: genealogy and religion. In terms of its application to Islamic law, the idea of kafa'ah is subject to two divergent perspectives. First, the situation in which nasab kafa'ah (huuree) is applied determines whether or not it is compatible with Islamic law. From the perspective of Islamic law, the prevalent religious kafa'ah appears harmonious.--Perkembangan Islam yang baik di tanah Papua turut mempengaruhi aspek adat dan budaya masyarakatnya, termasuk urusan pernikahan. Pokok permasalahan penelitian ini dibagi menjadi beberapa substansi permasalahan, yaitu: 1) Bagaimana gambaran umum pernikahan antara muslim Papua di Kelurahan Kaimana Kota? 2) Bagaimana penerapan kafa’ah dalam pernikahan antara muslim Papua ditinjau dari segi hukum Islam? Peneliti menggunakan jenis penelitian kualitatif deskriptif dengan metode field research (penelitian lapangan), dua pendekatan penelitian yaitu pendekatan sosial dan teologi-normatif (syar’i). Adapun sumber data penelitian ini adalah Al-Qur'an, hadis, beberapa masyarakat muslim Papua asli di Kelurahan Kaimana Kota. Selanjutnya, metode pengumpulan data yang digunakan adalah observasi, wawancara, dokumentasi serta penelusuran referensi. Kemudian, data diolah dan dianalisis dengan tiga tahapan, yaitu reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa gambaran pernikahan muslim Papua di Kelurahan Kaimana Kota sama dengan pernikahan masyarakat Indonesia umumnya kemudian ditambah dengan beberapa aturan adat yang mengikat prosesinya, di antaranya pemilihan jodoh, igiigree, nuhijna wafen, nobune muere, ukur hidung bagi anak perempuan, ijab dan qabul, dan nobune muere virnee naare. Kafa’ah yang berlaku terdiri dari dua poin utama yaitu nasab dan agama. Konsep kafa’ah dalam penerapannya dalam perspektif hukum Islam terbagi menjadi dua pendapat. Pertama, kafa’ah nasab (huuree) bisa selaras dan kurang selaras dengan hukum Islam sesuai dengan situasi penerapannya. Kedua, kafa’ah agama yang berlaku tampak selaras menurut perspektif hukum Islam.